Reliability and reproducibility of a rodent model of choroidal neovascularization based on the subretinal injection of polyethylene glycol - Ivan Fernandez-Bueno; Maria-Luz Alonso-Alonso; Maria-Teresa Garcia-Gutierrez; Yolanda Diebold (Molecular Vision, 2019)
Purpose: To evaluate the reliability and reproducibility of a rodent choroidal neovascularization (CNV) model by subretinal injection of polyethylene glycol (PEG).